Evaluación de Organihum y Rootex para desarrollo y mantenimiento radicular en el cultivo de tomate bajo invernadero - Caluguillin Caluguillin, Romel Eliceo (2022)
The root system is very important for any plant species but it is little studied, it should be noted that the largest amount of nutrients that a plant takes is from the soil and the organ in charge of this function is the root, hence its importance. For this reason, the present investigation was accelerated, which deals with the evaluation of rooting agents to promote the development and regeneration of the root system in the Pietro F1 Hybrid tomato crop, a DBCA was used, which consisted of three treatments, T1: rooting Organihum, T2: rooting Rootex and T3: the control, it was replicated four times with a total of 12 Experimental Units (UE). The doses used were those recommended on the label for Organihum was 2.5 mL/L and for Rootex 2.2 g/L, the applications were at 5 ddt, 12 ddt, 19 ddt, 34 ddt and 49 ddt. The variables studied were plant height (AP), physiological state (EF), length, weight, root volume (LR, PR, VR) and yield (R), no significant differences were found at 0.05 probability in the variables studied with the exception of the root volume for this case the best treatment was T1 (Organihum Rooting) 31.38 mL, in addition low relationships are found between the LR and R variable and this is attributed to T1 that presents a higher average with 30.75 cm. In this way, it is possible to mention the small functionality that Organihum Rooting has both in root development and maintenance and the relationship in terms of production, achieving good results